PERAN KOLABORASI SISTER CITY AS-JERMAN DALAM MEMBANGUN CLIMATE RESILIENCE - Nagari Yanottami; Diva Livia; Dyah Estu Kurniawati (Jurnal Sentris, 2022)
This phenomenon called "paradiplomacy" is used to accelerate the involvement of international cooperation by providing greater access to the state government. Therefore, the state is no longer the only actor, but local actors have begun to take over and participate in international relations activities for the benefit of their respective actors. The concept of Sister City or Twinning or often also called twin cities, is a collaboration between cities, which is formally agreed upon and binding as a long-term sister city. In this concept, any issue can be the theme of cooperation, including environmental and disaster issues. The great debate about paradiplomacy in IR studies arose in the Realist and Constructivism schools. This article examines other perspectives in international relations, namely Paradiplomacy and Sister city, as well as the interrelationships between these key concepts by reviewing previously written articles. This article is divided into several parts. First, the introduction of how the issue of climate change and the concept of sister cities in urban areas can be alternative adaptation and mitigation actions. Then the methodology and data sources used in this paper are described. Furthermore, these findings will be discussed with reference to the theoretical background. Finally, this paper outlines some conclusions and policy implications for the role of sister cities in the US-Germany to become cities that are resilient and resilient in facing climate change risks.